Effectiveness of Chemscrabb Media Games on Fundamental Laws of Chemistry Towards for Students' Learning Outcomes - Annisa Khairani Putri; Fajriah Azra; Elfa Hayati (Journal of Educational Chemistry (JEC), 2022)
The research aims to determine the effectiveness of Chemistry Scrabble (Chemscrabb) games as Instructional Media on Fundamental Laws of Chemistry to Students Learning Outcomes. This research is a research and development (RD) with designed by Posttest Only design, in which the design is based on the Thiagarajan technique. The research held on SMAN 10 Padang. Sampling selection was done by Random Cluster Sampling with the result that students of X-Science 2 as the experiment class and students of X-Science 4 as the control class. The data instruments used were a Post-test, questionnaire, and interview of two classes of the sample. The data analysis technique was a Hypothesis test by an Independent T-test sample. Based on Independent T-Test, the obtained tcount is 1.833, where the score is in the curve area, which means that accept H0 (there is no significant difference between the two samples). From the data, the research inference is that the utilization of Chemistry Scrabble (Chemscrabb) games as instructional media on Fundamental Laws of Chemistry for 10th-class sciences students is not effective for 10th-class sciences students' learning outcomes. However, students' activeness in the experiment class in the strengthening process (exercise) is higher than in the control class.